Distribution, abundance and habitat selection of Eriogaster catax (Linnaeus, 1758) in Álava (Spain) (Lepidoptera: Lasiocampidae) - F. de Juana; O. Aedo (SHILAP, 2021)
The presence of Eriogaster catax has been confirmed in 49 locations in the province of Álava and in three locations within the Condado de Treviño in the province of Burgos, corresponding to 27 UTM squares of 10 x 10 km. This brings the total number of known squares for Spain to 72, which represent a 53% increase with respect to the previous knowledge in this country. This species is widely distributed in the study area, occupying both the supratemperate and supramediterranean ecosystem layers. Nevertheless, density levels appear to be very low. With regard to habitat, this species exhibits a clear preference for gall-oak groves and their degradation stages, located mainly on the lower sections of mountain slopes and always on basic substrates. In every case, the species chosen for egg-laying were Crataegus monogyna or Prunus spinosa, in similar proportions.